Relationship Between Social Anxiety and Academic Performance among University Students - Muhammad Adil; Mazhar Iqbal Bhatti; Muhammad Imran (ASIAN Journal of International Peace & Security (AJIPS), 2022)
The present study examined the correlations between social anxiety and students’ academic performance. This research aimed to assess relationship between all facets of social anxiety and academic performance. The sample size was 203 which comprised 53.7 percent of female participants and 46.3 percent of male participants. Majority of the participants in the study were single (95.6percent) with middle socio economic status (94.1percent) and they belonged to Punjab Province (59.1%). The inter-items reliability of Leobitz Social Anxiety Scale was >.75. Moreover, the skewness and kurtosis values were ±2, which indicated the normal distribution of data’. Three valid and reliable instruments were used for data collection including, Liebowitz Social anxiet Scale (LSAS). The alpha reliability varies between 0.61 to 0.98 and Stroop test in psychology is used to assess the cognitive delay. The alpha reliability of Stroop test was 44.7 percent while its validity was reported 77.77percent. The results indicate that students who had high level of social anxiety had low academic achievement while those who had low level of anxiety show good academic performance. Female students score high on social anxiety and academic performance than male students.